Microarray Based Functional Analysis of Myricetin and Proteomic Study on Its Anti-Inflammatory Property. (7th March 2019) - Li, Tao; Zhu, Jihe; Deng, Fangming; Wu, Weiguo; Zheng, Zhibing; Lv, Chenghao; Li, Yong; Xiang, Wei; Lu, Xiangyang; Qin, Si
Abstract : Myricetin has been reported as a promising chemopreventive compound with multiple biofunctions. To evaluate its influence on gene expressions in genome-wide set and further investigate its anti-inflammatory property, the present study performed Gene Ontology and Ingenuity Pathway Analysis (IPA) to describe the basic gene expression characteristics by myricetin treatment in HepG2 cells, confirmed its multi-biofunction by real-time fluorescent quantitative PCR (RT-qPCR), and further verified its anti-inflammatory property by Western blotting and bio-plex-based cytokines assay. The IPA data showed that 337 gene expressions (48% of the top molecules) are disturbed over 2-fold, and the most possible biofunctions of myricetin are the effect on "cardiovascular disease, metabolic disease, and lipid metabolism, " via regulation of 28 molecules with statistic score of 46. RT-qPCR data confirmed the accuracy of microarray data, and cytokines assay results indicated that 6 of the total 27 inflammatory cytokine secretions were significantly inhibited by myricetin pretreatment, including TNF- α, IFN- γ, IL-1 α, IL-1 β, IL-2, and IL-6. The present study is the first time to elucidate the multi-function of myricetin in genome-wide set by IPA analysis and verify its anti-inflammatory property by proteomics of cytokines assay. Therefore, these results enrich the comprehensive bioactivities of myricetin and reveal that myricetin has powerful anti-inflammatory property, which provides encouragement for in vivo studies to verify its possible health benefits.